Peran Kepolisian dalam Penanggulangan Tindak Pidana Perdagangan orang di Polres Nabire. - I Nyoman Putra Sandita (CV. Syntax Corporation Indonesia, 2021)
Human trafficking is a terrible crime that leaves its victims traumatized. Human trafficking is a new form of slavery in which people are deceived and manipulated into being exploited. Many victims get into the human trafficking cycle as a result of the urgency of their economic troubles. Human trafficking is an instance where it is extremely difficult to prevent its spread because the extent of the problem has already reached national and international levels. The responsibility of the National Police in preventing human trafficking is critical. This study is a legal study that employs an empirical legal approach. The data in this study was gathered through interviews and literature review, after which analysed using descriptive qualitative methods.The National Police can take two steps in order to fulfil its job as a security and public order officer: preventive measures (prevention) and repressive measures (enforcement). In terms of preventive measures, the Nabire Resort Police Department has taken a number of steps to combat human trafficking. Specifically: 1) Restrict admittance to Nabire; 2) Embrace business owners (localization, café and karaoke proprietors); 3) Socializing; 4) Community approach; 5) Cooperation from all sides. In term of repressive actions, the Nabire Resort Police have undertaken two attempts: 1) Law enforcement efforts, Law enforcement shall be carried out in accordance with applicable laws, with Law Number 21 of 2007 serving as the ideal reference in this situation. However. Most human trafficking cases at Nabire Police Department are currently addressed through ADR; 2) Respond immediately to allegations or complaints from the public or reports from fellow officers at the crime scene.